2023
DOI: 10.3390/molecules28073144
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Exploitation of Synechocystis sp. PCC6803: A Cascade Approach for the Recovery of High Added-Value Products

Abstract: Microalgal biomass represents a very interesting biological feedstock to be converted into several high-value products in a biorefinery approach. In this study, the cyanobacterium Synechocystis sp. PCC6803 was used to obtain different classes of molecules: proteins, carotenoids and lipids by using a cascade approach. In particular, the protein extract showed a selective cytotoxicity towards cancer cells, whereas carotenoids were found to be active as antioxidants both in vitro and on a cell-based model. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similar results were obtained by Imbibo et al, who reported a 14% w / w PC extraction from wet biomass of Synechocystis sp. PCC 6803 by using 50 mM sodium acetate buffer (pH 5.5) and applying ultrasonication for cell disruption [ 38 ]. In the study of Avci et al [ 33 ], extraction of PC from lyophilized biomass of Synechocystis sp., using 0.01 M phosphate buffer (pH 7) and the FT method, was 0.4%, while when the bead-beating pretreatment method was applied, the extraction yield reached up to 17.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Imbibo et al, who reported a 14% w / w PC extraction from wet biomass of Synechocystis sp. PCC 6803 by using 50 mM sodium acetate buffer (pH 5.5) and applying ultrasonication for cell disruption [ 38 ]. In the study of Avci et al [ 33 ], extraction of PC from lyophilized biomass of Synechocystis sp., using 0.01 M phosphate buffer (pH 7) and the FT method, was 0.4%, while when the bead-beating pretreatment method was applied, the extraction yield reached up to 17.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Pigments were extracted using ethanol as solvent, as previously reported (Imbimbo et al 2023 ). Briefly, 200 mg of dry weight (D.W.) of alga were suspended in 4 mL of pure ethanol and disrupted by ultrasonication (40% amplitude, 4 min on ice, Bandelin SONOPULS HD 3200, tip MS73).…”
Section: Methodsmentioning
confidence: 99%
“…HaCaT cells were pre-treated with 90 μg/mL of ethanol extract for 2 h. Then, cells were stressed with 300 μM sodium arsenite (NaAsO 2 ) for 1 h as previously described (Sobeh et al 2019). Immediately after NaAsO 2 stress induction, intracellular ROS levels were determined by DCFDA assay, as previously reported (Imbimbo et al 2023), whereas intracellular glutathione (GSH) levels were measured by performing 5,5′-dithiobis-(2-nitrobenzoic acid) (DTNB) assay, as reported by (Laezza et al 2024).…”
Section: Sodium Arsenite Stress Induction and Biochemical Analysesmentioning
confidence: 99%